Purification of Xanthine Oxidase Inhibitor from Carica papaya leaves using Reversed Phase Flash Column Chromatography (RPFCC) - High Performance Thin Layer Chromatography (HPTLC) - Azmi, Saiful Mohammad Nizam; Jamal, Parveen; Amid, Azura (INSI Publications, 2012)
Xanthine oxidase (XO) is an enzyme that catalyses the metabolism of hypoxanthine and xanthine into uric acid. It is responsible for the medical condition known as gout, which is caused by the deposition of uric acid in the joints leading to painful inflammation. Inhibition of XO leads to remission in gout. Carica papaya is a member of the small family Caricaceae allied to the Passifloraceae. In folk medicine, Carica papaya has been used as an important traditional herbal medicine due to its vast bioactive compounds found including kaempferol, quercetin, 5, 7-dimethoxycoumarin, alkaloids, carpaine and pseudocarpaine. In this study, the dried mature leaves of Carica papaya was extracted with distilled water, optimized to obtain higher XO inhibitory activity, and the extract was subjected to reversed-phase flash column chromatography (RPFCC) and high performance thin layer chromatography (HPTLC) for the purification. Preliminary identification by chemical screening conducted on the optimized sample of distilled water extract of Carica papaya leaves showed the presence of several secondary metabolites, mainly, flavonoids, alkaloids, tannins, saponins and xanthine alkaloids, terpenoids and glycosides which could partially explain the pharmacological properties of this plant and demonstrates its importance in alimentation and daily intake especially for gout patient.